Customer Loyalty: Quality of Service - Apri Budianto (Magister Manajement Studies Program, 2019)
This article focuses on the influence of service quality on customer loyalty to modern market customers. This article is motivated by the increasing number of modern market customers caused by the quality of service that affects the increasing loyalty of customers. The formulation of the problem in this article is how the quality of service influence on customer loyalty. The working hypothesis in this article is: